Certificateless ciphertext retrieval scheme with multi-user and multi-keyword based on cloud-edge collaboration - Xiaodong YANG; Tian TIAN; Jiaqi WANG; Meijuan LI; Caifen WANG (Tongxin xuebao)
To solve the problems of single-user search, single-keyword search, high computational cost and low-security level of ciphertext data retrieval in the industrial Internet of things environment, a certificateless ciphertext retrieval scheme with multi-user and multi-keyword based on cloud-edge collaboration was proposed.A user access permissions table was set and once encryption algorithm was executed to realize multi-user search and update users’ access permissions.A cloud-side collaborative computing model was introduced to match keyword ciphertext and keyword trapdoor efficiently by a linear scanning method when the keyword ciphertext does not entirely contain the search keyword.Key escrow and certificate management problems were solved by utilizing certificateless encryption system.Keyword ciphertext authentication was ensured by using digital signature technology.The security analysis results show that the proposed scheme can resist internal keyword guessing attacks under the random oracle model.Simulation results show that the proposed scheme has higher computational efficiency compared with similar schemes.